PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS DISCOVERY LEARNING PADA MATERI PERSAMAAN GARIS LURUS - Ummul Khairani (Departemen Matematika, 2022)
This research aims to develop valid and practical student worksheet based on discovery learning model on the straight line equations. This is because the worksheets used in the learning process have not allowed students to participate in finding concepts or principles to build knowledge actively. This research uses the Plomp development model. There are three phases: the preliminary research phase, the development or prototyping phase, and the assessment phase. Data collection methods are interviews, observations, and questionnaires. Data from interviews and observations were analyzed using descriptive techniques. Questionnaire data were analyzed through descriptive statistics. The research results we received were valid and practical worksheets for students. Judging from the presentation aspect, content aspect, discovery learning model, display aspect, and linguistic aspect, the percentage value of the LKPD validity of 83,21% is included in the valid category. Worksheets are also practical because they are easy for students to use. The LKPD practicality ratio of 88,05% is included in the very practical category. Based on the research results, it can be concluded that the LKPD developed can be used for mathematics education in schools. Keywords – Student Worksheet, Discovery Learning, Straight Line Equations, Plomp